Linguistic finesse – Description of the phenomenon and an attempt at defining it - Głażewska, Milena (Papers in Linguistics, 2025)
The article focuses on the concept of ‘linguistic finesse,’ with the aim of proposing a precise definition of the term, which so far has often been vague and used intuitively in academic discourse. The text presents results of a study on the meaning of the lexeme ‘finesse,’ which involved a review of its usage in scholarly works and an extensive dictionary analysis, referencing numerous Polish and foreign language dictionaries. The undertaken research resulted in the development of a new definition of ‘linguistic finesse’ as a phenomenon recognized in linguistics. The analysis also considered Polish language corpora, which made it possible to provide deeper insight into the connotations of the term.